Advanced nodal stage predicts venous thromboembolism in patients with locally advanced non-small cell lung cancer. (June 2016) - Li, Richard; Hermann, Gretchen; Baldini, Elizabeth; Chen, Aileen; Jackman, David; Kozono, David; Nguyen, Paul; Nohria, Anju; Powell, Graham; Mak, Raymond
Abstract: Objectives: Patients with non-small cell lung cancer (NSCLC) are known to be at high risk for venous thromboembolism (VTE), but previous studies have not specifically analyzed locally advanced disease. We performed a retrospective VTE risk analysis in a cohort of locally advanced NSCLC treated with definitive intent including radiation therapy. Materials and methods: The cohort consisted of 629 patients with stage II–III NSCLC treated at a single institution from January 2003 to December 2012. All patients received treatment with curative intent, including radiation therapy. Fine and Gray's competing-risks regression model, accounting for death and distant metastasis as competing risks, was used to identify significant predictors of VTE risk, and cumulative incidence estimates were generated using the competing-risks model. Results and conclusion: At a median follow-up of 31 months, 127 patients developed a VTE, with 80% of events occurring in the first year after treatment initiation. 1-year and 3-year overall cumulative incidence estimates were 13.5% and 15.4%, respectively. On univariate analysis, stage IIIB and N3 nodal disease were associated with increased VTE risk. In the final multivariable model, N3 nodal disease was associated with increased VTE risk (Hazard ratio 1.64; 95% CI 1.06–2.54; p = 0.027). In conclusion, patients with locally advanced NSCLC are at high risk for VTE, especially in the first year after treatment initiation, with a 1-year cumulative incidence of 13.5%. N3 nodal staging was associated with significantly higher VTE risk compared to N0-N2 staging.